Modeling and usage of a sustainametric technique for measuring the life-cycle performance of a waste management system: A case study of South Africa - Aboginije, Ademilade; Aigbavboa, Clinton; Thwala, Wellington (Frontiers in Sustainability, 2023)
The use of eco-friendly materials, waste prevention protocols, the support and participation of building construction stakeholders, polluter pays concepts, producer responsibility, life-cycle system thinking, and the application of cost-efficiency and cost minimization strategies are some of the guiding philosophies that are of extreme value when designing a waste management system via circular economy initiatives. However, it is crucial to measure the waste management strategy used in each building project. In order to measure the life-cycle performance of waste management systems and to assess how sustainable they are, this study offers a statistical methodology using a sustainametric technique to indicate how sustainable waste management system performance in emerging construction industries, particularly in South Africa. This study employs a sustainametric approach to evaluate the life-cycle performance of the waste management system of South Africa, with evidence of its sustainability performance measurement that can help advance the its waste minimization policy and implementation. The result indicates the viability of the measuring model and the findings of each metric utilized. The conclusion confirms that South Africa has not fully adopted and/or implemented a more sustainable waste management system for efficient waste minimization during its construction activities. Moreover, it is the reality that most emerging economies urgently need to expand and improve the waste reduction method employed in its construction building projects.